Blueberry anthocyanins from commercial products: structure identification and potential for diabetic retinopathy amelioration - Li, Rui; Ye, Zhan; Yang, Wei; Xu, Yong Jiang; Tan, Chin Ping; Liu, Yuanfa (MDPI, 2022)
The aim of the present study was to determine the major anthocyanins of blueberry extracts from northeast China and explore their vision health improvement effects. HPLC-Q-TOF-MS/MS results suggested that six different anthocyanins were accurately identified, among which the Cy-3-glu (C3G) was the most abundant, ranging from 376.91 ± 7.91 to 763.70 ± 4.99 μM. The blueberry extract contained a higher purity of anthocyanins, and the anthocyanosides reached 342.98 mg/kg. The anti-oxidative stress function of C3G on HG-treated ARPE-19 cells were evaluated, and showed that the GSSG level of HG-cells pretreated with 10 μM C3G was significantly decreased, while the Nrf2 and NQO1 gene expression levels were increased. Further molecular docking (MD) results indicated that the C3G displayed favorable binding affinity towards REDD1, and only the B-ring of the C3G molecule displayed binding interactions with the CYS-140 amino acids within the REDD1 protein. It implied that the oxidative stress amelioration effects of C3G on the ARPE-19 cells were related to the REDD1 protein, which was probably via the Nrf2 pathways, although further studies are needed to provide mechanism evidence. The present study provides novel insights into understanding the roles of blueberry anthocyanins in ameliorating oxidative stress-induced BRB damage in the retina.